2018
DOI: 10.3390/ijms19020569
|View full text |Cite
|
Sign up to set email alerts
|

Effects of TROL Presequence Mutagenesis on Its Import and Dual Localization in Chloroplasts

Abstract: Thylakoid rhodanase-like protein (TROL) is involved in the final step of photosynthetic electron transport from ferredoxin to ferredoxin: NADP+ oxidoreductase (FNR). TROL is located in two distinct chloroplast compartments—in the inner envelope of chloroplasts, in its precursor form; and in the thylakoid membranes, in its fully processed form. Its role in the inner envelope, as well as the determinants for its differential localization, have not been resolved yet. In this work we created six N-terminal amino a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…). Previously, we have shown that imported TROL could not be extracted from membranes by high salt, urea, or high pH treatments, indicating that At4g01050 is an integral thylakoid membrane protein (Jurić et al , Vojta et al ). 6 M urea denatures unprotected proteins, 1 M NaCl disrupts electrostatic interactions between proteins and charged lipids, whereas high carbonate releases membrane‐associated/peripheral proteins.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…). Previously, we have shown that imported TROL could not be extracted from membranes by high salt, urea, or high pH treatments, indicating that At4g01050 is an integral thylakoid membrane protein (Jurić et al , Vojta et al ). 6 M urea denatures unprotected proteins, 1 M NaCl disrupts electrostatic interactions between proteins and charged lipids, whereas high carbonate releases membrane‐associated/peripheral proteins.…”
Section: Discussionmentioning
confidence: 95%
“…It has also been demonstrated that the chloroplast inner envelope translocon protein Tic62 anchors FNR (Küchler et al , Stengel et al , Benz et al , Alte et al , Lintala et al , Goss and Hanke 2014). TROL is synthesized on cytoplasmic ribosomes with N‐terminal chloroplast‐targeting presequence (amino acids 01‐69; Jurić et al , Vojta et al ). This sequence is cleaved prior to import into thylakoids, but not preceding the import into the inner envelope membrane of chloroplasts.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations